2D Flower-like CdS@Co/Mo-MOF as Co-Reaction Accelerator of g-C3N4-Based Electrochemiluminescence Sensor for Chlorpromazine Hydrochloride - Xiaowei Fan; Guping Zhang; Xiaodi Li; Yao Wang; Yi Wang; Shilei Hao; Defang Liu (Biosensors)
In this study, we have proposed an electrochemiluminescence (ECL) signal amplification system which is based on two-dimensional (2D) flower-like CdS@Co/Mo-MOF composites as a co-reaction accelerator of the g-C3N4/S2O82− system for ultrasensitive detection of chlorpromazine hydrochloride (CPH). Specifically, the 2D flower-like Co/Mo-MOF with mesoporous alleviated the aggregation of CdS NPs while simultaneously fostering reactant-active site contact and improving the reactant–product transport rate. This allowed the material to act as a novel co-reaction accelerator, speeding up the transformation of the S2O82− into SO4•− and enhancing the cathodic ECL emission of g-C3N4. Moreover, the signal probe which was synthesized by coupling the 2D CdS@Co/Mo-MOF and graphitic carbon nitride (g-C3N4) achieved the generation of SO4•− in situ and reduced energy loss. The results confirmed that the ECL signal was enhanced 6.2-fold and stabilized by CdS@Co/Mo-MOF. Based on the extremely strong quenching effect of chlorpromazine hydrochloride (CPH) on this system, a “signal-off” type sensor was constructed. The sensor demonstrated excellent sensitivity and linear response to CPH concentrations ranging from 1 pmol L−1 to 100 μmol L−1, with a low detection limit of 0.4 pmol L−1 (S/N = 3).